The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1108/ijshe-03-2015-0049
|View full text |Cite
|
Sign up to set email alerts
|

Connecting curriculum, capabilities and careers

Abstract: Purpose The reported research aims to examine the extent to which sustainability capabilities have been delivered by a specific example of Education for Sustainability (EfS) and Education for Sustainable Development (ESD), and how important the capabilities have been in the workplace. Design/methodology/approach Students who participated in an undergraduate internationally based research project were electronically surveyed. Questions sought responses related to demographics, the relevance of five “sustainab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…This mind-set trains creative and independent individuals with a tendency for innovation, who think independently and act cooperatively [35]. In the context of HESD, [36] research on five core capabilities that are related to sustainability has been carried out. They include system thinking (related to the ability to interconnect environmental, social, and economic perspectives), anticipatory (related to the ability to analyse future sustainable implications), regulatory (related to the timely use of sustainability knowledge regulation), and finally, strategic and interpersonal competences.…”
Section: Hesd Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…This mind-set trains creative and independent individuals with a tendency for innovation, who think independently and act cooperatively [35]. In the context of HESD, [36] research on five core capabilities that are related to sustainability has been carried out. They include system thinking (related to the ability to interconnect environmental, social, and economic perspectives), anticipatory (related to the ability to analyse future sustainable implications), regulatory (related to the timely use of sustainability knowledge regulation), and finally, strategic and interpersonal competences.…”
Section: Hesd Contextmentioning
confidence: 99%
“…Within the core competencies to be acquired by graduates they have incorporated the development of skills, such as effective communication to interact with different audiences, leadership, generation and assessment of solutions, critical thinking, open-mindedness, entrepreneurial spirit, logical reasoning, and willingness to interact as a team. The aforementioned skills are core capabilities related to HESD [36,37], which are also empowered by knowledge co-creation [43].…”
Section: Ecuadorian He Perspectivesmentioning
confidence: 99%
“…In order to design a pedagogical approach using sustainable technologies, Lockrey and Johnson [23] proposed a project-based learning (PBL) approach to build connections between an industry partner and students, and confirmed the impacts of such collaboration on cultivating students' deep knowledge and skills in the ever-evolving area of sustainability. Thomas and Depasquale [14] examined the importance of sustainability capabilities in the workplace and confirmed that a problem-based learning curriculum can be effective in delivering five capabilities: namely, system thinking, anticipatory, normative, strategic, and interpersonal skills. Etse and Ingley [6] analyzed the higher education curriculum for sustainability in Ghana and appealed for more deliberate efforts to integrate sustainability in the curriculum.…”
Section: Industry-oriented Sustainability-related Curriculum Designmentioning
confidence: 94%
“…The Australian Department of Education, Employment, and Workplace Relations mentions that professional and vocational skills are sustainability skills required for green jobs across all industry sectors as a response to climate change and sustainability imperatives [14]. Accordingly, preparing business students to possess capabilities relevant to sustainability is a primary goal of higher education institutions; thus, designing sustainability-related curricula conforming to business needs is a critical task for such institutions.…”
Section: Introductionmentioning
confidence: 99%
“…Teaching experiences in accounting education at a university in southwest England used to enhance students' knowledge about sustainability and teamwork (Wyness and Dalton 2018). Engineering programs are offered at Aalborg University in Denmark (Holgaard et al 2016) and at RMIT University in Australia (Thomas and Depasquale 2016). At the graduate level, Ban et al (2015) sketch several cases in which PBL is integrated into education for sustainability.…”
Section: Problem-based Learning In Sustainability Education and Entrementioning
confidence: 99%